Competency: An Introduction - Mohammad, Hairuddin; Hassan, Padzil Fadzil; Yaman, Siti Khalijah (Multidisciplinary Applied Research and Innovation, 2021)
Competency or competence for some others is getting much attention in the past few decades, especially in the literature of management strategy. It was understood that the term is usually associated with training and educational fields. Unfortunately, there were occasions of misunderstanding on the appropriate usage for the term, at least within the realm of the Malaysian construction industry. Therefore, the paper presents a brief review of competency in order to unfold the concept of competency. The paper posits that skills, knowledge, and abilities (including attitudes) became the primary elements when discussing what is inside the “competency”. Nevertheless, it needs to be discussed along with its intended usage, function, and amid its appropriate contexts, with the purpose of having the most suitable meanings.